Enhancing the international regulation of science innovators: reputation to the rescue?. Issue 1 (2nd January 2019) - Devaney, Sarah
ABSTRACT: This article argues that the use of reputation-affecting regulatory measures can enhance efforts to regulate research in the biotechnology sector at an international level by increasing actors' inclination to comply and by encouraging the culture of the sector to become one in which 'science solidarity' is embedded. It characterises the sector as having a number of features which both make such reputation-affecting measures necessary as well as suggesting that they are likely to be effective. Drawing on examples of regulatory compliance and non-compliance in the sector, this article demonstrates that reputation-affecting measures can complement existing regulatory frameworks and draw on and develop existing cultures within the international community of scientists and stakeholders to enhance the likelihood of compliance with regulatory and scientific norms.